Cellulolytic and xylanolytic actinomycetes selection to degrade lignocellulosic biomass of robusta coffee pulp (Coffea canephora) - Putri, Eka; Rukayadi, Yaya; Sunarti, Titi Candra; Meryandini, Anja (Institute of Physics Publishing, 2019)
Actinomycetes are bacteria that have a high ability to produce hydrolytic enzymes that can be applied to degrade coffee pulp which contains lignocellulose components. Coffee pulp is residues from a coffee industry that can be used as substrates in the solid state fermentation process. In this study, cellulase and xylanase activity from actinomycetes isolates were investigated. Screening of these enzymes activity was using agar medium supplemented with 1% carboxymethylcellulose (CMC) and xylan from beechwood as substrate. Production of clear zones surrounding isolates on CMC and xylan agar medium was considered as indicative of extracellular cellulase and xylanase activity. The size of a transparent zone diameter was considered as proportional to the level of cellulase and xylanase production. Congo red 0,1% was used for staining. Selected actinomycetes isolates were continued to growth investigation on agar medium supplemented with 1% coffee pulp. The clear zone formed around isolates indicated that the isolate had the ability to degrade the lignocellulose component in the coffee pulp. The results show that of the 99 actinomycetes isolates tested on agar medium supplemented with 0.1% CMC and xylan, 16 isolates showed cellulase activity (cellulase index ≥ 2), 20 isolates showed xylanase activity (xylanase index ≥ 1), and 5 isolates showed both activities. Ten isolates have the ability to grow and produce a clear zone on the coffee pulp agar medium with cellulase and xylanase activity. Among these ten tested isolates; HJ4.5b, P2b(b).3, P2b(b).4, and P2b(b).18 are the most potential isolates that can be continued for further research on fermentation coffee cherries.